2020
DOI: 10.1108/jhti-05-2020-0092
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of accessibility in tourism websites: a pledge towards disability

Abstract: PurposeThe purpose of this paper is to analyse the US states and territories’ official tourism information websites based on the Web Content Accessibility Guideline (WCAG) and Section 508 guidelines to identify the compliance of websites towards disabilities policies and their behaviour pattern.Design/methodology/approachThe official tourism websites of 57 states and territories were analysed through the TAW tool for WCAG 2.0 and AChecker for Section 508. Cluster analysis was used to produce a group of website… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…More recently, some studies concerning the topic of web accessibility in hospitality and tourism have also considered the WCAG 2.0 guidelines. In the USA, Singh et al (2020) 2020) investigated accessibility factors in fourand five-star hotel units in Greece. The results of this study revealed that, despite websites containing up-todate information, the WCAG 2.0 standards were applied in a very small percentage of hotels examined.…”
Section: Hotel Web Accessibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, some studies concerning the topic of web accessibility in hospitality and tourism have also considered the WCAG 2.0 guidelines. In the USA, Singh et al (2020) 2020) investigated accessibility factors in fourand five-star hotel units in Greece. The results of this study revealed that, despite websites containing up-todate information, the WCAG 2.0 standards were applied in a very small percentage of hotels examined.…”
Section: Hotel Web Accessibilitymentioning
confidence: 99%
“…More recently, some studies concerning the topic of web accessibility in hospitality and tourism have also considered the WCAG 2.0 guidelines. In the USA, Singh et al (2020) evaluated the official tourism websites of 57 states and territories, detecting different issues in several WCAG 2.0 guidelines. In a European context, Kous and Polančič (2021) analysed web accessibility issues in official tourism websites of 26 European Union Member States, detecting at least one failure in every website.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accessibility has taken center stage as a tool for inclusion and achieving tourism for all (Buhalis and Darcy, 2010; Darcy and Dickson, 2009; Rucci et al , 2021, 2022). The literature has also seen a shift in focus to digital accessibility in the past few years (Casais and Castro, 2021; Domínguez Vila et al , 2019; Eusébio et al , 2020; Fontanet Nadal and Jaume Mayol, 2011; Lestari et al , 2019; Shi, 2006; Silveiro et al , 2019; Singh et al , 2021; Teixeira et al , 2021; Williams and Rattray, 2005). In addition, accessibility is a complex concept that is still open to debate (Fernández-Díaz et al , 2021; Lestari et al , 2019; Madeira et al , 2021; Nitti, 2018; Ribeiro et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In international literature, research on tourism for individuals with disabilities mainly focuses on accessibility and travel behaviour. In terms of accessibility issues, research is related to online access to information resources [1][2][3][4][5][6], the limitations of individuals with disabilities in tourism activity [7][8][9][10][11], as well as the barriers that individuals with disabilities face [12,13]. Also, in terms of travel behavior issues, research is related to the analysis of the needs and motivations of people with disabilities [14][15][16][17][18], the evaluation of the behavior of tourists with disabilities [19][20][21][22][23], the evaluation of information sources for accommodation [24][25][26], and the evaluation of hospitality services in specific tourist destinations [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%